Biocatalytic Syntheses of Antiplatelet Metabolites of the Thienopyridines Clopidogrel and Prasugrel Using Fungal Peroxygenases - Kiebist, Jan; Schmidtke, Kai-Uwe; Schramm, Marina; König, Rosalie; Quint, Stephan; Kohlmann, Johannes; Zuhse, Ralf; Ullrich, René; Hofrichter, Martin; Scheibner, Katrin (Journal of fungi (Basel), 2021)
Antithrombotic thienopyridines, such as clopidogrel and prasugrel, are prodrugs that undergo a metabolic two-step bioactivation for their pharmacological efficacy. In the first step, a thiolactone is formed, which is then converted by cytochrome P450-dependent oxidation via sulfenic acids to the active thiol metabolites. These metabolites are the active compounds that inhibit the platelet P2Y12 receptor and thereby prevent atherothrombotic events. Thus far, described biocatalytic and chemical synthesis approaches to obtain active thienopyridine metabolites are rather complex and suffer from low yields. In the present study, several unspecific peroxygenases (UPOs, EC 1.11.2.1) known to efficiently mimic P450 reactions in vitro—but requiring only hydroperoxide as oxidant—were tested for biocatalytic one-pot syntheses. In the course of the reaction optimization, various parameters such as pH and reductant, as well as organic solvent and amount were varied. The best results for the conversion of 1 mM thienopyridine were achieved using 2 U mL−1 of a UPO from agaric fungus Marasmius rotula (MroUPO) in a phosphate-buffered system (pH 7) containing 5 mM ascorbate, 2 mM h−1 H2O2 and 20% acetone. The preparation of the active metabolite of clopidogrel was successful via a two-step oxidation with an overall yield of 25%. In the case of prasugrel, a cascade of porcine liver esterase (PLE) and MroUPO was applied, resulting in a yield of 44%. The two metabolites were isolated with high purity, and their structures were confirmed by MS and MS2 spectrometry as well as NMR spectroscopy. The findings broaden the scope of UPO applications again and demonstrate that they can be effectively used for the selective synthesis of metabolites and late-state diversification of organic molecules, circumventing complex multistage chemical syntheses and providing sufficient material for structural elucidation, reference material, or cellular assays.